The Challenge of Democracy in Indonesia: The Case of Salafi Movement - Din Wahid (Islamika Indonesiana, 2014)
In spite of strong support of the majority of Muslims in Indonesia to democratic system, there are small numbers of Muslim who reject the democratic system. To name a few, I can mention here some groups of Muslims who oppose the democracy, such as Hizbut Tahrir Indonesia (HTI), Majelis Mujahidin Indonesia (MMI) and Salafis. These groups maintain that democracy is against Islam, because Islam does not recognize democracy. Democracy as symbolized by “the power of people” contradicts the basic doctrine of Islam concerning the sovereignty. In Islam, they maintain, the power or sovereignty belongs to God only. This essential concept creates various consequences dealing with governance of the ruled. This paper discusses the views of Salafis in Indonesia on the democracy. Despite their resistance of democracy, the Salafis consider a ruler resulted from democracy is valid, and Muslims should obey him: they are not allowed to criticize him publicly, and are not allowed to rebel against him.